Colorimetric Determination of Baclofen with Ninhydrin Reagent and Compare with HPLC Method in Tablet - JALAL HOSSEINIMEHR*, SEYED; POURMORAD, FERESHTEH; MOSHTAGHI, EHSAN; AMINI†, MOHSEN (Asian Journal of Chemistry, 2024)
A simple and sensitive spectrophotometeric method has been developedfor the determination of baclofen in tablet. Baclofen reacts withninhydrin reagent in aqueous solution producing a coloured product.In this study, the different experimental parameters affecting the developmentand stability of the colour were carefully studied and optimized.The modified HPLC with ion pair method was used for quantificationof baclofen in the same tablets that used with spectrophotometery. Theabsorbance-concentration plot is linear over the range 0.4-1.4 mg/mLwith correlation coefficient of 0.995. The molar absorptive was 283.36mol/L cm. The validity of the described procedures was assessed toshow that this method had good validity at different times. Statisticalanalysis of the results has been carried out with F-test and T-test showedthat it has high accuracy with HPLC method, but it has not good precisioncompared to HPLC method.